A 15-year follow-up of transfemoral amputees with bone-anchored transcutaneous prostheses: mechanical complications and patient-reported outcomes. (January 2020) - Hagberg, Kerstin; Ghassemi Jahani, Shadi-Afarin; Kulbacka-Ortiz, Katarzyna; Thomsen, Peter; Malchau, Henrik; Reinholdt, Carina
Abstract : Aims: The aim of this study was to describe implant and patient-reported outcome in patients with a unilateral transfemoral amputation (TFA) treated with a bone-anchored, transcutaneous prosthesis. Methods: In this cohort study, all patients with a unilateral TFA treated with the Osseointegrated Prostheses for the Rehabilitation of Amputees (OPRA) implant system in Sahlgrenska University Hospital, Gothenburg, Sweden, between January 1999 and December 2017 were included. The cohort comprised 111 patients (78 male (70%)), with a mean age 45 years (17 to 70). The main reason for amputation was trauma in 75 (68%) and tumours in 23 (21%). Patients answered the Questionnaire for Persons with Transfemoral Amputation (Q-TFA) before treatment and at two, five, seven, ten, and 15 years' follow-up. A prosthetic activity grade was assigned to each patient at each timepoint. All mechanical complications, defined as fracture, bending, or wear to any part of the implant system resulting in removal or change, were recorded. Results: The Q-TFA scores at two, five, seven, and ten years showed significantly more prosthetic use, better mobility, fewer problems, and an improved global situation, compared with baseline. The survival rate of the osseointegrated implant part (the fixture) was 89% and 72% after seven and 15 years, respectively. A total of 61 patients (55%) had mechanical complications (mean 3.3 (SD 5.76)), resulting in exchange of the percutaneous implant parts. There was a positive relationship between a higher activity grade and the number of mechanical complications. Conclusion: Compared with before treatment, the patient-reported outcome was significantly better and remained so over time. Although osseointegration and the ability to transfer loads over a 15-year period have been demonstrated, a large number of mechanical failures in the external implant parts were found. Since these were related to higher activity, restrictions in activity and improvements to the mechanical properties of the implant system are required. Cite this article: Bone Joint J 2020;102-B(1):55–63